Subsurface damage from helium ions as a function of dose, beam energy, and dose rate - Livengood, Richard; Tan, Shida; Greenzweig, Yuval; Notte, John; McVey, Shawn (Journal of vacuum science & technology. B, Microelectronics and nanometer structures processing, measurement and phenomena, 2009)
In recent years, helium ion microscopy has produced high resolution images with novel contrast mechanisms. However, when using any charged particle beam, one must consider the potential for sample damage. In this article, the authors will consider helium ion induced damage thresholds as compared to other more traditional charged-particle-beam technologies, as a function of dose, dose rate, and beam energy, and describe potential applications operating regimes.